Konsep Zuhud al-Qushayrî dalam Risâlah al-Qushayrîyah - Moh. Fudholi (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2011)
The purpose of this study is to gain comprehensive information about the concept of zuhd that is explained in Risâlah al-Qushayrîyah authored by al-Qushayrî. The study is formulated within the concept and history of zuhd, namely zuhd as a maqâm (stage) and zuhd as an akhlâq (moral). The research uses an interpretation method. According to al-Qushayri, zuhd is resignation to Allah Himself. The correct zuhd will lead to virtuous morals.